Business is Blooming: An Inquiry into the Development of the Dane County Farmers? Market and the Factors of its Success - Manitakos, Troy; Tolle, Ben; Davies, Amanda; Dahl, Casey (My University, 2011)
The Dane County Farmers Market is a special part of our lives living in Madison, Wisconsin and we want to know, what trends in the region influenced the development of the Dane County Farmer's Market (DCFM) and what factors can we attribute to its success? Our research consisted of an interview with DCFM Manager Larry Johnson and a review of twenty-five newspaper articles. In our paper we highlight four major factors that we found to have the most influence and contribution to the current success of the DCFM. The increasing trend of eating local in Wisconsin is a major factor of success as local food is rooted in the geography and people of Wisconsin. Additionally, the increase in marketing of local producers aides in facilitating the relationships between producers and consumers. Vendors at the DCFM can only sell goods that they themselves produce. This is an integral part of the market because the DCFM is currently the largest producer-only farmers market in the nation. The critical location of the market, around the Capitol Square, aids in the promotion of the market and creates a unique phenomenon that brings consumers to downtown Madison. The market also is an important community center for Madison, bringing together individuals and groups with interests in various political and social issues. In identifying these characteristics of a successful farmers' market and exploring their value, we hope that these factors will encourage and enhance farmers markets both in Madison and elsewhere.
Includes Maps, Images, Figures, Appendix and Bibliography.
Keywords: Local Food; Madison, WI; Farmers Market; Dane County